2022
DOI: 10.1002/acm2.13507
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of an automatic atlas‐based segmentation tool for male pelvis CT images

Abstract: This retrospective work aims to evaluate the possible impact on intraand inter-observer variability, contouring time, and contour accuracy of introducing a pelvis computed tomography (CT) auto-segmentation tool in radiotherapy planning workflow. Methods: Tests were carried out on five structures (bladder, rectum, pelvic lymph-nodes, and femoral heads) of six previously treated subjects, enrolling five radiation oncologists (ROs) to manually re-contour and edit auto-contours generated with a male pelvis CT atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In our study, we found that a large atlas library size was not necessary for ABAS automatic contouring and an atlas library size of 20 could be enough to insure the accuracy of automatic contouring with the ABAS method. However, some authors validated ABAS based on a higher number of subjects for male pelvis CT images compared to what is concluded in the present article (20,21). Some authors validated ABAS based on a lower number of subjects for prostate cancers if compared to what is concluded in the present article (7,11).…”
Section: Discussionmentioning
confidence: 57%
“…In our study, we found that a large atlas library size was not necessary for ABAS automatic contouring and an atlas library size of 20 could be enough to insure the accuracy of automatic contouring with the ABAS method. However, some authors validated ABAS based on a higher number of subjects for male pelvis CT images compared to what is concluded in the present article (20,21). Some authors validated ABAS based on a lower number of subjects for prostate cancers if compared to what is concluded in the present article (7,11).…”
Section: Discussionmentioning
confidence: 57%
“…The clinical validity of AI-defined OARs evaluated by Dice and HD95 has been assumed in prostate ( 39 ) including in physician-edited contours in a prospective study ( 40 ). The current study has demonstrated limited value in Dice and HD95, and therefore introduces a more stringent comparison metric, HD<1mm.…”
Section: Discussionmentioning
confidence: 99%
“…51 Generally, good autosegmentation performance is achieved if results are as good or better than interobserver variability, which was shown to range from 0.8 to 0.99 for the pelvic region. 124 Consequently, Sun et al and Zhao et al demonstrated Dice score agreement greater than 0.89 for the pelvic region. 46,47 Recently, segmentation-specific studies have compared the performance of CBCT-derived sCT images for abdominal segmentations, reporting Dice scores above 0.8.…”
Section: Recommendations For Cliniciansmentioning
confidence: 99%